Preliminary crystallographic analysis of the Escherichia coli YeaZ protein using the anomalous signal of a gadolinium derivative - Jeudy, Sandra (International Union of Crystallography, 2005)
The Escherichia coli yeaZ gene encodes a 231-residue protein (M (r) = 25 180) that belongs to a family of proteins that are conserved in various bacterial genomes. This protein of unknown function is predicted to be a hypothetical protease. The YeaZ protein was overexpressed in E. coli and crystallized at 298 K by the hanging-drop vapour-diffusion method. A MAD data set was collected using a gadolinium-derivative crystal that had been soaked with 0.1 M Gd-DOTMA. The data set contained data collected to a resolution of 2.7 Å at two wavelengths at the L (III) absorption edge of gadolinium, while remote data were collected to a resolution of 2.28 Å. The crystal belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 76.3, b = 97.6, c = 141.9 Å. Phasing using the MAD method confirmed there to be four monomers in the asymmetric unit related by two twofold axes as identified by the self-rotation function search.